LINGUISTIC HYBRIDITY AND DEVELOPMENTAL PERSPECTIVES IN CAMEROON - Alobwede, Charles Esambe (International Journal of Research -GRANTHAALAYAH, 2021)
Language politics and the issue of official bilingualism have been factors in Cameroonian politics since the country obtained independence from its respective colonial masters. These phenomena have impacted not only on the operation of state institutions, but also on the cultural and linguistic make-up of the society. This has given birth to cultural and linguistic and perspectives in development. French and English, the two official languages of the country and a legacy of colonialism have created linguistic and sometimes political, social and cultural barriers. Bilingualism, a policy adopted by the government of Cameroon to achieve national unity and integration has often been criticized because of some of its shortcomings. However, this article seeks to prove that despite such shortcomings, cultural and bilingualism have positively impacted the political, historical, economic, social and cultural factors of development in Cameroon.